2021
DOI: 10.1177/2058460120981001
|View full text |Cite
|
Sign up to set email alerts
|

Meningioma uptake of 68Gallium-PSMA-11 as a pitfall on positron emission tomography/computer tomography

Abstract: Prostate cancer is the most common malignancy in men with high incidence of recurrence following treatment. Biochemical recurrence, as indicated by rising PSA levels following successful treatment of the primary disease, is a frequent encounter in routine clinical practice. 68Gallium-PSMA positron emission tomography/computer tomography has been widely accepted as the modality of choice with the highest impact in management of this group of patients. Pitfalls of this diagnostic technique stem from the diversit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Gupta et al also reported a parietal lobe meningioma that demonstrated avid 68 Ga-PSMA uptake, and diagnosis was supported by MRI [75]. Courtney et al reported a patient with a history of prostate cancer who demonstrated 68 Ga-PSMA uptake in the left frontal lobe, confirmed as a preexisting meningioma [76]. Finally, Junqueira et al reported avid 68 Ga-PSMA uptake (SUV max 12.1) in an MRI-detected lesion, suggestive of an intraventricular meningioma of a patient with history of prostate cancer [77].…”
Section: Resultsmentioning
confidence: 99%
“…Gupta et al also reported a parietal lobe meningioma that demonstrated avid 68 Ga-PSMA uptake, and diagnosis was supported by MRI [75]. Courtney et al reported a patient with a history of prostate cancer who demonstrated 68 Ga-PSMA uptake in the left frontal lobe, confirmed as a preexisting meningioma [76]. Finally, Junqueira et al reported avid 68 Ga-PSMA uptake (SUV max 12.1) in an MRI-detected lesion, suggestive of an intraventricular meningioma of a patient with history of prostate cancer [77].…”
Section: Resultsmentioning
confidence: 99%
“…These findings were confirmed by multiple studies that reported expression of PSMA in many solid tumors, primary gliomas, and brain metastases ( 6–10 ). In addition, case reports are becoming more frequent in which maintenance imaging of patients with a known history of prostate cancer with 68GA PSMA-11 has led to the incidental finding of PSMA-avid meningiomas ( 4 , 21 ).…”
Section: Discussionmentioning
confidence: 99%